2016
DOI: 10.1542/peds.2015-3741
|View full text |Cite
|
Sign up to set email alerts
|

Global Varicella Vaccine Effectiveness: A Meta-analysis

Abstract: CONTEXT: Several varicella vaccines are available worldwide. Countries with a varicella vaccination program use 1-or 2-dose schedules. OBJECTIVE:We examined postlicensure estimates of varicella vaccine effectiveness (VE) among healthy children.DATA SOURCES: Systematic review and descriptive and meta-analysis of Medline, Embase, Cochrane libraries, and CINAHL databases for reports published during 1995-2014. STUDY SELECTION:Publications that reported original data on dose-specific varicella VE among immunocompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
140
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(170 citation statements)
references
References 52 publications
11
140
1
10
Order By: Relevance
“…Alternatively, the addition of a second dose provides protection against all severities [25]. The economics of implementing one- or two-dose schedules have been widely debated [20,26,27], but national choices will ultimately depend on whether their priorities are varicella elimination or prevention of severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the addition of a second dose provides protection against all severities [25]. The economics of implementing one- or two-dose schedules have been widely debated [20,26,27], but national choices will ultimately depend on whether their priorities are varicella elimination or prevention of severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since this recommendation, two-doses of VV have been shown to provide greater protection than one-dose (67), with varicella incidence, hospitalisations, and outbreaks all having declined (230, 231). Over 2.5 years the VE of two-doses of VV in preventing varicella was 98% compared to 86% VE of a singledose, and a relative VE in two versus one-dose recipients of 95% (67), similar findings to a recent meta-analysis of international studies on varicella VE (232).…”
Section: Discussionsupporting
confidence: 79%
“…A second dose of VV not only reduces risk of infection and interrupts virus transmission (232), it also appears to lower subsequent risk of developing zoster (67). However, the costeffectiveness and incremental benefits of a second-dose needs to be considered in context with funding of all drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 42 epidemiological studies of varicella immunisation in immunocompetent patients showed 81% effectiveness after one dose (95% CI 78% to 84%) and 92% after two doses (95% CI 88% to 95%) 5. Subgroup analysis revealed higher effectiveness in preventing more severe cases of varicella (98% effectiveness; 95% CI 97% to 99%).…”
Section: Does the Vaccine Work?mentioning
confidence: 99%